Keterkaitan Pengalaman Kewirausahaan, Sikap, Norma Subyektif, Kontrol Perilaku terhadap Niat untuk menjadi Wirausahawan (Studi pada perajin batik di kota surakarta, kabupaten sragen dan kabupaten karanganyar) - Firmansyah, Bagus (Sekolah Tinggi Ilmu Ekonomi Atma Bhakti, 2013)
The purpose of this study was to examine the influence of attitudes on perceived desirability, the influence of entrepreneurial experience on perceived desirability and perceived feasibility, the influence of subjective norm on perceived desirability and perceived feasibility, the influence of perceived behavior control on perceived feasibility, and than the influence of perceived desirability and perceived feasibility on the intention to become an entrepreneur. The existence of previous research is still little research on entrepreneurship intentions with planned behavior theory and the entrepreneurial event theory on crafters or workers, so it is motivating researchers to conduct this research. Sample was 120 batik artisans in Surakarta, Sragen and Karanganyar. Sampling technique with purposive sampling method. The statistical methods used to test the validity, reliability, and the research hypothesis is the approach to Structural Equation Modeling (SEM). Results of this study indicate that attitudes have no effect on the perceived desirability. Entrepreneurial experience has no influence on perceived desirability. Entrepreneurial experience has no influence on perceived feasibility. Subjective norm has a positive influence on perceived desirability. Subjective norm has a positive influence on perceived feasibility. Control behavior has an influence on perceived feasibility. Perceived desirability to have a positive influence on intentions to become entrepreneurs. Perceived feasibility has no effect on the intention to become an entrepreneur.